DAMPAK KOMPENSASI EKSEKUTIF TERHADAP AGRESIVITAS PAJAK PERUSAHAAN DI INDONESIA (Studi Empiris pada Perusahaan yang Terdaftar di Indeks Kompas 100 BEI Tahun 2017-2021) - Sekar Ayu Cahyaningtyas; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2023)
This study aims to examine the sensitive effect on tax aggressiveness of companies listed on the Indonesia Stock Exchange in 2017-2021. The variables used in this study include the dependent variable (company tax aggressiveness), independent variable (executive compensation), moderating variable (corporate governance strength), and control variable (size, profitability, leverage, capital intensity, growth, foreign activity, R&D intensity, operating and industry volatility). The population used in this study are companies listed on the Indonesia Stock Exchange in 2017-2021. By using purposive sampling in selecting the sample, a total of 97 research samples were obtained for 5 consecutive years (2017-2021). The research hypothesis uses panel data regression analysis method. The findings from this study indicate a significant positive relationship between variable executive compensation and tax aggressiveness. This study indicate a significant negative relationship between fixed executive compensation and tax aggressiveness. The effect of the variable executive compensation on corporate tax aggressiveness show significant positive results, either with or without moderation of corporate governance strength. However, the moderating effect of corporate governance strength shows an insignificant positive result on the relationship between fixed executive compensation and corporate tax aggressiveness.